"We have to put the fire out first before we start rebuilding the house": practitioners' experiences of supporting women with histories of substance use, interpersonal abuse and symptoms of post-traumatic stress disorder. (3rd July 2020) - Bailey, Karen; Trevillion, Kylee; Gilchrist, Gail
Abstract: Introduction and aims: The high prevalence of women experiencing co-occurring substance use, interpersonal abuse, and symptoms of post-traumatic stress disorder (PTSD) has led to international calls for trauma-specific substance use treatments and wider trauma-informed practice. The aim of this study was to explore how services in England have developed practice responses with limited historical precedence for this work. Design and Methods: A purposive sample of 14 practitioners from substance use, interpersonal violence and criminal justice services were chosen for their integrated practice. Semi-structured interviews exploring their understanding of the co-occurring issues, staged treatment models and wider trauma-informed practice, and the challenges associated with this. Thematic analysis was employed. Results: Three key interlinking themes were identified: practitioners' philosophical approach; tailored clinical practice, and system responsiveness . Analyses identified the importance of relational, non-pathologising practice, extensive focus on physical and emotional safety, and cautionary approaches towards using trauma-specific treatments involving trauma disclosure. Challenges included poor service integration, time-limited treatments and tokenistic trauma informed practice. Discussion: Practitioners from across disciplines emulated important components of trauma-informed practice and promoted a 'safety-first' approach reliant on multi-agency working and wider system responses. Trauma-specific interventions required skilled and experienced practitioners, and longer treatment programmes comprising first stage work. Conclusions: In the context of limited gender-responsive substance use treatment in the UK, practitioners demonstrated integrated practice that supported the recommended staged PTSD model and trauma-informed practice. Organisational leadership and support from service commissioners and funders are recommended to promote growth of this approach across the UK.